Mao Zedong zhuxi he Dalai Lama, Banchan E'erdeni zai yiqi guo zangli muyang xinnian
'Chairman Mao, the Dalai Lama and the Panchen Lama E'erdeni celebrate the new Wooden Goat Year of the Tibetan lunar calendar together.' Printno. M8049.43. Title in Chinese and Tibetan.